Shifts in soil microbial and nematode communities over progression of pine wilt disease occurring in Pinus koraiensis stands - Tian, Siyu; Wang, Mingwei; Dong, Xin; Ji, Yuting; Wu, Hao; Koski, Tuuli-Marjaana; Wang, Minggang; Li, Qi (Frontiers in Microbiology, 2025)
IntroductionPine wilt disease (PWD) is recognized as a destructive forest disease worldwide, leading to massive mortality of many Pinus spp., including the Korean white pine Pinus koraiensis. Current work has focused on underlying development of this disease occurring aboveground, but few studies have assessed soil consequences from the destruction in pine forest by PWD.MethodsIn this study, we collected soil samples from one stand of PWD-resistant species Larix olgensis, and from four stands of PWD-susceptible P. koraiensis (n = 8) following a natural chronosequence of PWD development (healthy, diseased, killed, and clear-cut P. koraiensis). We aimed to investigate the shifts in soil microbial and nematode communities under the canopy of P. koraiensis over the PWD progression.ResultsThe α-diversity e.g., species richness of bacterial community in soil of healthy P. koraiensis was ca. 17% lower than in soil of diseased pines. The species richness of fungal community in the soil of healthy P. koraiensis was also 24.5% lower than in soil of killed pines. The diseased and killed pines also exhibited different compositions in soil microbial community from the healthy pines, although these damaged trees did not differ themselves in the composition. In particular, the relative abundance of the methane-cycling Methylomirabilota became higher in bacterial community and the ectomycorrhizal Agaricomycetes was lower in fungal community in soil of the diseased or killed pines than healthy ones, suggesting an overall decrease in soil health caused by PWD. Although the α-diversity of soil nematode community did not vary over the development of PWD, its composition was significantly altered by the disease. Consequently, we observed a lower inter-kingdom network complexity in the soil community of the pines following the PWD, in which the bacterial networks decreased but fungal networks increased in complexity. The nematode community also showed a lower network complexity in soil of PWD-destructed pines, albeit that this only occurred when the pines were diseased rather than killed.DiscussionBy recording the structure dynamics of soil microbial and nematode communities in pines following the progression of PWD, this study helps to understand the impacts of PWD on soil biotic processes, thus providing an important reference for better assessing the ecological consequences of this devastating disease.